Developing a sustainable destination policy framework for Indonesia’s spice route: balancing heritage conservation and tourism development - Wanadjaja, Timotheus Lesmana; Rahmanita, Myrza; Mariati, Sri; Riyadi, Agus (Technium Social Sciences Journal, 2026)
Indonesia’s historic Spice Route represents an invaluable cultural heritage asset with significant potential for sustainable tourism development. This research examines the development of a comprehensive policy framework for transforming Indonesia’s Spice Route into a network of sustainable tourism destinations that balance heritage conservation with economic development. The study employed a qualitative methodology combining in-depth interviews, direct observations, and document analysis across three strategic locations: the Banda Islands, Banten, and Aceh, selected for their historical significance in international spice trade networks. Data collection involved multiple stakeholders including government officials from the Ministry of Education and Culture, tourism managers, local communities, and industry practitioners. Findings reveal that Indonesia possesses exceptional spice heritage assets, including 60 species of valuable spices, historical trading infrastructure, and rich culinary traditions that offer significant tourism potential. However, seventeen major challenges impede sustainable development, with infrastructure and facility limitations, public awareness deficits, stakeholder coordination issues, ineffective promotional strategies, environmental concerns, and funding constraints identified as primary barriers. The research concludes that successful Spice Route tourism development requires integrated policy interventions that address institutional capacity, infrastructure development, community empowerment, and promotional strategies simultaneously. The proposed policy framework provides a roadmap for leveraging Indonesia’s unique spice heritage while ensuring sustainable economic benefits, cultural preservation, and environmental stewardship.